Post-harvest quality changes and shelf-life determination of washed and blanched sugar kelp (Saccharina latissima) - Wirenfeldt, Cecilie Bay; Sørensen, Jonas Steenholdt; Kreissig, Katharina Johanna; Hyldig, Grethe; Holdt, Susan Løvstad; Hansen, Lisbeth Truelstrup (Frontiers in Food Science and Technology, 2022)
Sugar kelp (Saccharina latissima) is a native European brown macroalga with the potential to become a vital part of the green transition of the food industry. Knowledge of the sugar kelp shelf-life is essential to designing the food supply chain to ensure safe and high-quality food. Establishing a single-compound quality index (SCQI) of freshness would be useful for the industry. However, information is currently lacking on how different post-harvest treatments affect the shelf-life of sugar kelp, even though it is important knowledge for manufacturers, authorities and consumers. The objective of this study was to establish the shelf-life of refrigerated sugar kelp following five post-harvest treatments and evaluate the effect of these treatments on changes in quality attributes (sensory, microbial, chemical and physical) during storage to select the SCQI. The post-harvest treatments included washing in sea water, washing in potable water, blanching for 2 min in sea water or potable water and untreated sugar kelp. Based on sensory analysis, the refrigerated (+ 2.8°C) shelf-lives for sugar kelp from all treatments were seven to 9 days. The end of the sensory shelf-life correlated with the development of >7 log (CFU g−1) aerobic viable counts, suggesting this attribute can be used as a SCQI to evaluate the shelf-life of sugar kelp. The microbiota was dominated by putative spoilage organisms from the Pseudoalteromonadaceae and Psychromonadaceae families. Untreated and washed sugar kelp continued to respire and consume carbohydrates up to 5 days post-harvest, indicating respiration rates may be used to determine freshness of non-blanched kelp. Favorable organoleptic properties, e.g., sweetness and umami, decreased during storage and coincided with a reduction in water-soluble mannitol and free glutamic acid. Both blanching treatments changed texture and color and reduced iodine and vitamin C contents while retaining components such as fucoxanthin, chlorophyll a and β-carotene. This study provides crucial documentation of quality changes during the post-harvest storage period of sugar kelp, including information about sugar kelp spoilage and nutrient changes, which would facilitate the development of best practices for manufacturers using sugar kelp in their production of food.